Obispo, financista y político: el doctor don Feliciano de Vega y Padilla (1580-1641) - Gálvez Peña, Carlos M. (2012)
Don Feliciano de Vega y Padilla (1580-1641) was one of the most distinguished members of the Peruvian colonial episcopate in the first half of the seventeenth century, and the only one who, after an outstanding ecclesiastical career, was appointed archbishop of Mexico. His passionate life, professional profile and intellectual production make Don Feliciano an interesting case study in order to understand the complex and tense dynamics of power linking Royal Patronage and the most important religious and political institutions in the city of Lima during the early colonial period. The study of Dr. Vega’s life and work also shedslight on the first generation of colonial intellectuals who debated the rights of Creole subjects. The works written by Bishop Vega constitute some of the first written expressions of the defense of prelacies and offices within the colonial Church, and the debate over the doctrine of Distributive Justice which was used to justify these claims. This article analyzes the relationship between Bishop Vega and the principal viceregal institutions: the university, the archbishopric, the cathedral chapter and the Royal Audience. Finally, it will analyze how Lima’s elite citizens, of which Vega was one, manipulated these institutions.